Solve for n 2(1.5n+4)-6n=-7

Math
2(1.5n+4)-6n=-7
Simplify 2(1.5n+4)-6n.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
2(1.5n)+2⋅4-6n=-7
Multiply 1.5 by 2.
3n+2⋅4-6n=-7
Multiply 2 by 4.
3n+8-6n=-7
3n+8-6n=-7
Subtract 6n from 3n.
-3n+8=-7
-3n+8=-7
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Subtract 8 from both sides of the equation.
-3n=-7-8
Subtract 8 from -7.
-3n=-15
-3n=-15
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3n=-15 by -3.
-3n-3=-15-3
Cancel the common factor of -3.
n=-15-3
Divide -15 by -3.
n=5
n=5
Solve for n 2(1.5n+4)-6n=-7

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top